Analogues of Pseudomonas aeruginosa signalling molecules to tackle infections - Ó Muimhneacháin, E.; Reen, F.; O'Gara, Fergal; McGlacken, G. (Royal Society of Chemistry, 2018)
© 2017 The Royal Society of Chemistry. The emergence of antibiotic resistance coupled with the lack of investment by pharmaceutical companies necessitates a new look at how we tackle bacterial infections. An intriguing tactic is the interruption of bacterial communication systems. This non-biocidal approach would circumvent the evolutionary pressure on bacteria to mutate and develop resistance. In many pathogenic microorganisms, communication systems, collectively termed quorum sensing (QS), have been observed to control a number of bacterial behaviours including expression of virulence factors and the development of biofilms. QS signalling molecules and their biomimetics, therefore, represent a rational target for the disruption of cooperative behaviour and thus the development of novel antimicrobial strategies. Herein we review recent developments towards the interference of Pseudomonas aeruginosa QS using signalling molecules and their mimetics.